Inherited macular degeneration-associated mutations in CNGB3 increase the ligand sensitivity and spontaneous open probability of cone cyclic nucleotide-gated channels - Meighan, Peter C.; Peng, Changhong; Varnum, Michael D. (Frontiers in Physiology, 2015)
Cyclic nucleotide gated (CNG) channels are a critical component of the visual transduction cascade in the vertebrate retina. Mutations in the genes encoding these channels have been associated with a spectrum of inherited retinal disorders. To gain insight into their pathophysiological mechanisms, we have investigated the functional consequences of several CNGB3 mutations, previously associated with macular degeneration (Y469D and L595F) or complete achromatopsia (S156F, P309L, and G558C), by expressing these subunits in combination with wild-type CNGA3 in Xenopus oocytes and characterizing them using patch-clamp recordings in the inside-out configuration. These mutations did not prevent the formation of functional heteromeric channels, as indicated by sensitivity to block by L-cis-diltiazem. With the exception of S156F, each of the mutant channels displayed electrophysiological properties reflecting enhanced channel activity at physiological concentrations of cGMP (i.e., a gain-of-function phenotype). The increased channel activity produced by these mutations resulted from either increased functional expression levels, or increased sensitivity to cyclic nucleotides. Furthermore, L595F increased the spontaneous open probability in the absence of activating ligand, signifying a ligand independent gain-of-function change. In addition to the CNGB3 disease-associate mutations, we characterized the effects of several common CNGB3 and CNGA3 single-nucleotide polymorphisms (SNPs) on heteromeric CNGA3+CNGB3 channel function. Two of the SNPs examined (A3-T153M, and B3-W234C) produced decreased ligand sensitivity for heteromeric CNG channels. These changes may contribute to background disease susceptibility when combined with other genetic or nongenetic factors. Together, these studies help to define the underlying molecular phenotype for mutations relating to CNG channel disease pathogenesis.